Crop Residue Management in Cotton - Ramanjaneyulu, A. V.; Ramprasad, B.; Sainath, N.; Umarani, E.; Pallavi, Ch.; Vijay, J.; Jagadeeshwar, R. (Chronicle of Bioresource Management, 2021)
Cotton is the most important commercial crop across rainfed growing regions in India. It produces kapas which has wide variety of uses in industry. Besides, it leaves lot of residues which include stalks, locules, leaves and roots in the field after picking kapas. A huge quantity of residue is being generated across different cotton growing states in India and a large portion of it is being burnt on-farm primarily to clear the field for sowing succeeding crops and for clean cultivation. But, it is leading to environmental pollution and emission of green houses gases. Further, valuable plant material is being lost which otherwise can be used for productive purposes. Many researchers found that insitu incorporation of crop residue would enrich soil fertility, enhances crop productivity and conserves the environment. This paper discussed various machinery with main emphasis on multi crop shredder and also different options for managing the cotton residues effectively.